Weight of salivary gland ultrasonography compared to other items of the 2016 ACR/EULAR classification criteria for Primary Sjögren's syndrome. (12th November 2019) - Jousse‐Joulin, S.; Gatineau, F.; Baldini, C.; Baer, A.; Barone, F.; Bootsma, H.; Bowman, S.; Brito‐Zerón, P.; Cornec, D.; Dorner, T.; de Vita, S.; Fisher, B.; et al.
Abstract: Objective: Major salivary gland ultrasonography (SGUS) is widely used for the diagnosis of primary Sjögren's syndrome (pSS). Our objective was to assess the contribution of SGUS compared to other items of the 2016 ACR/EULAR pSS classification criteria, based on expert opinion. Methods: A secure web‐based relational database was used by 24 experts from 14 countries to assess 512 realistic vignettes developed from data of patients with suspected pSS. Each vignette provided classification criteria items and information on history, clinical symptoms and SGUS findings. Each expert assessed 64 vignettes, and each vignette was assessed by 3 experts. A diagnosis of pSS was defined according to at least 2 of 3 experts. Validation was performed in the independent French DiapSS cohort of patients with suspected pSS. Results: A criteria‐based pSS diagnosis and SGUS findings were independently associated with an expert diagnosis of pSS ( P < 0.001). The derived diagnostic weights of individual items in the 2016 ACR/EULAR criteria including SGUS were as follows: anti‐SSA, 3; focus score ≥ 1, 3; SGUS score ≥ 2, 1; positive Schirmer's test, 1; dry mouth, 1; and salivary flow rate < 0.1 mL/min, 1. The corrected C statistic area under the curve for the new weighted score was 0.96. Adding SGUS improves the sensitivity from 90.2 % to 95.6% with a quite similar specificity 84.1% versus 82.6%. Results were similar in the DiapSS cohort: adding SGUS improves the sensitivity from 87% to 93%. Conclusion: SGUS had similar weight compared to minor items, and its addition improves the performance of the 2016 ACR/EULAR classification criteria. Abstract :